PENGARUH TUNTUTAN AKADEMIK DAN BEBAN KERJA TERHADAP KESEHATAN MENTAL MAHASISWA PRODI BIMBINGAN DAN KONSELING UNIVERSITAS TEKNOLOGI YOGYAKARTA - Alda Kirantika Putri; Ari Prasetyoaji (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Academic demands are where it refers to a series of expectations, standards and requirements that must be met by individuals who are involved in higher education. Workload is a process in determining the number of hours of human resources that work, are used, and are needed in completing a job for a certain period of time. High academic demands and workloads are often associated with negative impacts on mental health. These negative impacts include stress, anxiety and even depression. This research method is a research with a descriptive quantitative approach. Data collection using questionnaires and using the Depression Anxiety Stress Scale-21 (Dass-21) research instrument. The sample in this study was 19 students according to the research criteria, sampling using purposive sampling techniques. Based on the results of the study, there were students who experienced moderate academic demands and moderate workloads, while the results of mental health research showed that there were students who experienced depression and stress at normal levels, but experienced anxiety at very severe levels. Based on the results of multiple regression tests, a significance value of 0.00 <0.05 was obtained, meaning that there is an influence between the variables of academic demands and workload on the mental health of students of the Guidance and Counseling Study Program, Universitas Teknologi Yogyakarta.